SOUND CONVERSION USING FAST FOURIER TRANSFORM ALGORITM - Hendrawan, Tan Ferrdy (Universitas Katolik Soegijapranata, 2017)
The goal of voice conversion is to change the data of a sound file. By changing the data, the octave of the sound can also be changed to higher or lower octave. One of the methods that being used in sound conversion is Fast Fourier Transform algoritm. Fast Fourier Transform algorithm is used to process the sound data. The processed sound data will be written on a new sound file.